Explaining Interview Duration in Web Surveys: A Multilevel Approach. (April 2015) - Gummer, Tobias; Roßmann, Joss
Interview duration is an important variable in web surveys because it is a direct measure of the response burden. In this article, we analyze the effects of the survey design, respondent characteristics, and the interaction between these effects on interview duration. For that purpose, we applied multilevel analysis to a data set of 21 web surveys on political attitudes and behavior. Our results showed that factors on both levels, the individual and the survey level, had effects on interview duration. However, the larger share of the variation in interview duration is explained by the characteristics of the respondents. In this respect, we illustrate the impact of mobile devices and panel recruitment on interview duration. In addition, we found important relationships between the respondents' attitudes and how a web survey is designed: Highly motivated respondents spent significantly more time answering cognitively demanding questions than less motivated respondents. When planning a survey, not only the number and formats of questions need to be taken into account but also the expected sample composition and how the participants will respond to the design of the web survey.